2013
DOI: 10.3109/10641963.2012.758734
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative Effects of Valsartan and Amlodipine on vWf Levels and N/L Ratio in Patients with Newly Diagnosed Hypertension

Abstract: High levels of circulating Von Willebrand factor (vWf) and increased neutrophil to lymphocyte (N/L) ratio may reflect vascular inflammation in hypertensive patients. In present study, we aimed to investigate the effects of valsartan as an angiotensin II receptor antagonist and amlodipine as a calcium channel blocker on the vWf levels and N/L ratio in patients with essential hypertension. Patients were randomized to one of the following intervention protocols: calcium channel blocker (amlodipine, 5-10 mg/day) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
67
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 26 publications
2
67
0
Order By: Relevance
“…The N/L ratio is also an inflammatory marker of major adverse cardiac events (9). However, sometimes acute conditions like bacterial or viral infections, chronic inflammatory disease and drug treatments might affect neutrophil and lymphocyte counts and so the ratio of these parameters might be changed (10). Therefore, N/L ratio itself alone without other inflammatory markers may not give information to clinicians about the chronic endothelial inflammatory condition of the patient.…”
Section: Thach Nguyenmentioning
confidence: 99%
See 1 more Smart Citation
“…The N/L ratio is also an inflammatory marker of major adverse cardiac events (9). However, sometimes acute conditions like bacterial or viral infections, chronic inflammatory disease and drug treatments might affect neutrophil and lymphocyte counts and so the ratio of these parameters might be changed (10). Therefore, N/L ratio itself alone without other inflammatory markers may not give information to clinicians about the chronic endothelial inflammatory condition of the patient.…”
Section: Thach Nguyenmentioning
confidence: 99%
“…Multislice computed tomography angiography (MSCTA) is a very useful and an important tool for the noninvasive evaluation, intervention and cure of coronary arterial pathology (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). We present the assessment of three patients with coronary artery disease (a 88-year old man, 62 -year old man and 66 year-old man, using a MSCTA coronary angiography (64-320 slice technology), that was firstly described by Leschka S (5).…”
Section: Thach Nguyenmentioning
confidence: 99%
“…Furthermore, it has been shown that antihypertensive medications might also affect NLR levels. 13,14 In a study including 72 newly diagnosed patients with hypertension, Fici et al 13 showed that nebivolol has significantly reduced the NLR levels after 6 months of treatment period. In conclusion, the results of the study by Uysal et al 1 showed that higher levels of NLR were associated with poor CCC in stable CAD, but these results should be interpreted with some limitations, particularly statin and antihypertensive therapy among the study groups.…”
mentioning
confidence: 99%
“…Antihypertensive therapy like nebivolol, valsartan and amlodipine significantly lowered the NLR. 8,12 In this context, medication should be considered, when the NLR is assessed.…”
mentioning
confidence: 99%